Experimental Study on the Elemental Sulfur Solubility in Sour Gas Mixtures - Zhang, Rui; Gu, Shaohua; Huang, Liang; Zeng, Daqian; Li, Tong; Zhang, Guangdong (Frontiers in Earth Science, 2021)
The investigation of elemental sulfur solubility plays critical roles on sour gas reservoir development. In this paper, the solubility of elemental sulfur was directly measured by static method with gas samples from well M1 of a sour gas reservoir in Sichuan Basin. The results show that the solubility of elemental sulfur ranges from 0.001 g/cm3 to 0.968 g/cm3 at 40~98.9 MPa and 15~49.8 MPa. The elemental sulfur solubility increases with increasing temperature and pressure, especially when the pressure is greater than 30 MPa. Moreover, the H2S content in sour gas mixtures is also an important factor affecting elemental sulfur solubility. The elemental sulfur solubility increases with increasing H2S content of the sour gas mixtures. The experimental data in this paper display a consistent trend with the reported experimental data. Based on the experimental results, the chrastil-type model, Robert’s model and Hu’s model were investigated and compared. The results show that the chrastil-type model by fitting experimental data in this paper has less error and higher accuracy in calculating elemental sulfur solubility in M gas reservoir. The chrastil-type models proposed in the literature, meanwhile, are only based on the regression of specific gas components and experimental conditions, which lead to a large error in the calculation of elemental sulfur solubility of sour gas samples in this research. The research results provide important basic data and technical support for the development of M gas reservoir.